Transcriptional profile and Epstein-Barr virus infection status of laser-cut immune infiltrates from the brain of patients with progressive multiple sclerosis - Veroni, Caterina (J Neuroinflammation, 2018)
BACKGROUND: It is debated whether multiple sclerosis (MS) might result from an immunopathological response toward an active Epstein-Barr virus (EBV) infection brought into the central nervous system (CNS) by immigrating B cells. Based on this model, a relationship should exist between the local immune milieu and EBV infection status in the MS brain. To test this hypothesis, we analyzed expression of viral and cellular genes in brain-infiltrating immune cells. METHODS: Twenty-three postmortem snap-frozen brain tissue blocks from 11 patients with progressive MS were selected based on good RNA quality and prominent immune cell infiltration. White matter perivascular and intrameningeal immune infiltrates, including B cell follicle-like structures, were isolated from brain sections using laser capture microdissection. Enhanced PCR-based methods were used to investigate expression of 75 immune-related genes and 6 EBV genes associated with latent and lytic infection. Data were analyzed using univariate and multivariate statistical methods. RESULTS: Genes related to T cell activation, cytotoxic cell-mediated (or type 1) immunity, B cell growth and differentiation, pathogen recognition, myeloid cell function, type I interferon pathway activation, and leukocyte recruitment were found expressed at different levels in most or all MS brain immune infiltrates. EBV genes were detected in brain samples from 9 of 11 MS patients with expression patterns suggestive of in situ activation of latent infection and, less frequently, entry into the lytic cycle. Comparison of data obtained in meningeal and white matter infiltrates revealed higher expression of genes related to interferonγ production, B cell differentiation, cell proliferation, lipid antigen presentation, and T cell and myeloid cell recruitment, as well as more widespread EBV infection in the meningeal samples. Multivariate analysis grouped genes expressed in meningeal and white matter immune infiltrates into artificial factors that were characterized primarily by genes involved in type 1 immunity effector mechanisms and type I interferon pathway activation. CONCLUSION: These results confirm profound in situ EBV deregulation and suggest orchestration of local antiviral function in the MS brain, lending support to a model of MS pathogenesis that involves EBV as possible antigenic stimulus of the persistent immune response in the central nervous system. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-017-1049-5) contains supplementary material, which is available to authorized users.